Political Losers as a Barrier to Economic Development - Acemoglu, Daron; Robinson, James A (American Economic Review, 2000)
Per-capita income in many sub-Saharan African countries, such as Chad and Niger, is less than 1/30th of that of the United States. Most economists and social scientists suspect that this is in part due to institutional failures that stop these societies from adopting the best technologies. A particularly interesting historical example comes from the di®usion of railways in the nineteenth century. While railways are regarded as a key technology driving the industrial revolution, there were large lags in its di®usion. For example, in 1850 the United States had 14,518km of track, Britain 9,797km and Germany 5,856km, in the Russian and Hapsburgh Empires there were just 501km and 1,357km, respectively (all data from Mitchell, 1993). Why do societies, as in this example, fail to adopt the best available technologies? One answer is that existing powerful `interest groups ' block the introduction of new technologies in order to protect their economic rents, and societies are able to make technological advances only if they can defeat such groups. Economic monopolies may be one example. A monopolist might wish to block the intro-